2018
DOI: 10.1007/s11099-018-0844-2
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium stress in Dongying wild soybean seedlings: growth, Cd accumulation, and photosynthesis

Abstract: In order to understand better Cd resistance in soybean, Dongying wild soybean treated with different Cd concentrations were evaluated. The biomass, chlorophyll (Chl) content, leaf color, Chl a fluorescence parameters, photosynthesis parameters, and Cd contents were determined. Our results showed that when Cd concentration was ≤ 2 kg m -3 , no significant decrease in biomass, photosynthetic parameters, and maximal photochemical efficiency of PSII was observed. This indicated that Dongying wild soybean resisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Under single and combined stress, the TF was less than 1, further confirming the results. These results are similar to those of Liu et al [56]. However, in our study, there was no obvious accumulation in various parts of the D. involucrata plants when the Pb concentration was high.…”
Section: Accumulation and Translocation Of Pb And CD In D Involucratasupporting
confidence: 92%
“…Under single and combined stress, the TF was less than 1, further confirming the results. These results are similar to those of Liu et al [56]. However, in our study, there was no obvious accumulation in various parts of the D. involucrata plants when the Pb concentration was high.…”
Section: Accumulation and Translocation Of Pb And CD In D Involucratasupporting
confidence: 92%
“…Photosynthesis, one of the most important biological processes for plant growth and food production, is especially sensitive to Cd stress [76][77][78][79]. As shown in Figure 4, the net photosynthetic rate (Pn), stomatal conductance (Gs), transpiration rate (Tr), and intercellular CO 2 concentration (Ci) in the leaves of L. japonica under different treatments were evaluated.…”
Section: The Effect Of Electric Field On Photosynthetic Parametersmentioning
confidence: 99%
“…Under Cd stress, plants often show growth inhibition and biomass reduction [38,39]. It has been reported that the suppression of plant growth is one of the most crucial characteristics in plants under Cd stress [40].…”
Section: Discussionmentioning
confidence: 99%